A Case Report on Antibiotics Induced Skin Rashes in a Tertiary Care Hospital in Southern Odisha - Panda, Suvendu Kumar; Pradhan, Mousumi; Dash, Snehasini; Mahanta, Jasmine (Student's Journal of Health Research Africa, 2025)
Background: Antibiotics, while essential in treating infections, are also among the most common causes of cutaneous adverse drug reactions (ADRs), especially in pediatric populations. This report presents two pediatric cases of antibiotic-induced skin rashes following administration of ceftriaxone and vancomycin. Case Presentation: Case 1 involves a 9-month-old male with left-sided empyema who developed erythematous rashes within one hour of receiving intravenous ceftriaxone. The reaction was managed with intramuscular antihistamine (Pheniramine), and ceftriaxone was discontinued. Case 2 reports a 9-year-old male with pyrexia of unknown origin, who developed widespread rashes after 13 days of vancomycin therapy. The reaction was suspected to be a delayed-type hypersensitivity. Vancomycin was discontinued and intravenous methylprednisolone was initiated. Causality Assessment: Both reactions were assessed as “probable” according to the WHO-UMC Causality Assessment Scale. Discussion: These cases highlight the potential of beta-lactam (ceftriaxone) and glycopeptide (vancomycin) antibiotics to induce immediate and delayed cutaneous hypersensitivity reactions. While often underreported, these reactions can be managed effectively with prompt drug withdrawal and appropriate treatment. The importance of vigilant pharmacovigilance, especially in pediatric settings, is emphasized. Conclusion: Antibiotic-induced skin reactions in children warrant early identification, rational drug use, and avoidance of re-exposure. Strengthening pharmacovigilance practices and conducting larger studies can aid in better understanding and prevention. Recommendations: Routine monitoring of pediatric patients on antibiotics for hypersensitivity symptoms, detailed allergy history-taking, timely reporting to pharmacovigilance programs, and patient/caregiver education are essential. Rechallenge with the suspected drug should be avoided.